Creation of the Structure and Mechanical Properties of Tungsten Heavy Alloys for Special Application - Mieczysław KACZOROWSKI; Paweł SKOCZYLAS (Problemy Mechatroniki)
The paper presents the results of experimental studies aimed at elaboration of the manufacturing technology of tungsten heavy alloys (WSC) with high mechanical properties, dedicated for kinetic energy penetrators of armour piercing fin stabilized discarding sabot (APFSDS) ammunition. Especially, the results of mechanical properties’ investigations and structure observations of the materials strengthened by cold work and heat treatment involving supersaturation and aging are described. It was concluded that the best method of WSC strengthening is cold working, involving strain hardening both tungsten grain and Ni-based matrix. The cold working should be carried out under control because it excesses deformation causing very high strength and hardness increase is accomplished by the cost of substantial ductility, especially impact strength decrease. The solution heat treatment in vacuum furnace followed by water quenching and then isothermal aging at temperature range of 500-800°C enable further strength and hardness increase of WSC but its effectiveness is substantially less than cold work strengthening.